(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2022)
Kappaphycus alvarezii is one of the seaweed species which is mostly developed in coastal areas and has a highly economic value. Development areas that pay attention to the suitability and carrying capacity indicators of the waters is an effort that can be done to ensure the sustainability of this species production in the future. This study aims to analyze the development area of seaweed farming based on the suitability and carrying capacity indicators. This study was conducted in the coastal of Baubau City, Southeast Sulawesi Province, from February to March 2020. Data on physical and chemical parameters of the waters were collected directly at the research site to determine suitability categories, while the concentration of nitrate (NO3-) that can be uptake by seaweed is obtained from available secondary data. Environmental parameter data was processed using software image processing with weight sum overlay method and continued with carrying capacity analysis based on the nitrate absorption of seaweed. The results of the analysis suitability category obtained reached 3114.9 ha, with the most suitable category covering 1033.3 ha and the suitable category 2081.6 ha. The carrying capacity of the nitrate concentration that can be accommodated by the waters is 0.497 kg-N/day, with the total amount of seaweed that can be cultivated is 7317.90 tons. Most of the coastal waters area of Baubau City has the potential to be utilized as a seaweed aquaculture development area with a high amount of production.